EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT), JIGSAW II DAN THINK PAIR SHARE (TPS) PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KECERDASAN EMOSIONAL SISWA SMP NEGERI DI KABUPATEN SUKOHARJO - Stefy Erlinda Novalia; Mardiyana Mardiyana; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purpose of this study was to determine the effect of learning models on student’s mathematics achievement viewed from emotional quotient. The learning models compared were learning model of the Numbered Heads Together (NHT), Jigsaw II, and TPS. This research was a quasi-experimental research. The population of the research was all of the eighth grade students of the State Junior High School in Sukoharjo. The instrumentsused to collect data were mathematics achievement and emotional quotient questionnaire. Technique of analyzing data that used was unbalanced two ways analysis of variance. From the research, it can be concluded as follows. (1) Learning by using cooperative learning model of Jigsaw II and NHT gave better mathematics learning achievement than learning by using cooperative learning model of TPS, learning by using cooperative learning model of NHT gave better mathematics learning achievement than learning by using cooperative learning model of TPS. (2) Students who have high emotional quotient gave better mathematics learning achievement than students who have middle and low emotional quotient, students who have middle emotional quotient gave better mathematics learning achievement than students who have low emotional quotient, (3) On the cooperative learning model of Jigsaw II, students who have high and middle emotional quotient gave better mathematics learning achievement with the students who have low emotional quotient. On the cooperative learning model of NHT, students who have high emotional quotient gave better mathematics learning achievement with the students who have low emotional quotient. On the cooperative learning model of TPS, students who have high, middle and low emotional quotient gave the same mathematics learning achievement. (4) On the high emotional quotient, using cooperative learning model of learning by Jigsaw II, NHT and TPS gave the same mathematics learning achievement. On the middle emotional quotient, using cooperative learning model of learning by Jigsaw II gave better mathematics learning achievement with learning by using cooperative learning model of TPS. On the low emotional quotient, using cooperative learning model of learning by Jigsaw II, NHT and TPS gave the same mathematics learning achievement.Keywords: Cooperative learning model, Jigsaw II, NHT, TPS, mathematics learning achievement, emotional quotient.